Abuse of Power Dalam Kasus Kerangkeng Manusia oleh Mantan Bupati Langkat: Kajian Hukum dan HAM - Rizkitiana, Ratu Amelia; Emiliyanti, Nabilla Lutfiah; Qotrunada, Raisya Shafa; Bhaskara, Haryo; Hayya, Aisya Anjani Nurul; Suot, Glorya Meyhoa; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The unlawful detention case involving former Regent of Langkat, Terbit Rencana Perangin-angin, exemplifies a severe abuse of power leading to significant human rights violations. This article identifies various forms of this abuse and analyzes them from a human rights perspective, referencing national laws, such as Law No. 39 of 1999, and international instruments like the Convention Against Torture and ILO Convention No. 29 on forced labor. Using a qualitative approach and literature review, the study finds that the practices of unlawful detention, torture, and labor exploitation in the private prison constitute serious human rights violations, including potential human trafficking. This case highlights the inadequacies in oversight and accountability among local officials and underscores the urgent need for a comprehensive evaluation of Indonesia's human rights protection systems. The article recommends strengthening supervisory institutions, enforcing strict legal actions against offenders, and formulating policies to prevent similar abuses in the future.